Dispositional mindfulness mediates the relations between neuroticism and posttraumatic stress disorder and depression in Chinese adolescents after a tornado. (July 2019) - An, Yuanyuan; Fu, Gan; Yuan, Guangzhe; Zhang, Qian; Xu, Wei
Previous studies have shown that neuroticism is associated with higher levels of posttraumatic stress disorder (PTSD) and depression in individuals who have experienced traumatic events. This study investigated dispositional mindfulness as one pathway in which neuroticism is related to PTSD and depression symptoms among Chinese adolescents who have experienced trauma by considering the role of dispositional mindfulness. Participants were 443 Chinese adolescents who had experienced a severe tornado a year prior to this study. The results showed that our model fitted the data well ( χ 2 /df = 2.113, comparative fit index (CFI) = 0.981, Tucker–Lewis index (TLI) = 0.969, root mean square error of approximation (RMSEA) (90% confidence interval (CI)) = 0.061 [0.047, 0.080]) and revealed that dispositional mindfulness partially mediated the relationship between neuroticism and PTSD and depression symptoms. The clinical implications and limitations of our research and recommendations for future research are discussed in this article.